2017
DOI: 10.1088/1361-648x/aa9455
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic multiplexing of solid-state nanopores

Abstract: Although solid-state nanopores enable electronic analysis of many clinically and biologically relevant molecular structures, there are few existing device architectures that enable high-throughput measurement of solid-state nanopores. Herein, we report a method for microfluidic integration of multiple solid-state nanopores at a high density of one nanopore per (35 µm). By configuring microfluidic devices with microfluidic valves, the nanopores can be rinsed from a single fluid input while retaining compatibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…It has been shown that nanopores with diameters down to 1 nm can identify single molecules 15 or significantly enhance supercapacitor capacitance 10 . With continuous decrease of the pore diameter from sub-micrometer to below 1 nm, various factors dominate ion transport through the pores, such as surface charge density 16 , ion-ion interactions 17 and size effect 18 ; and the current-voltage relation may display distinct linear, voltage-activated or rectified current, and different cation-selectivity profiles 16 . In fact, once the pore diameter is reduced to less than 2 nm, sub-continuum ion transport has been observed 17,19 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that nanopores with diameters down to 1 nm can identify single molecules 15 or significantly enhance supercapacitor capacitance 10 . With continuous decrease of the pore diameter from sub-micrometer to below 1 nm, various factors dominate ion transport through the pores, such as surface charge density 16 , ion-ion interactions 17 and size effect 18 ; and the current-voltage relation may display distinct linear, voltage-activated or rectified current, and different cation-selectivity profiles 16 . In fact, once the pore diameter is reduced to less than 2 nm, sub-continuum ion transport has been observed 17,19 .…”
Section: Introductionmentioning
confidence: 99%
“…In principle, these devices can be used for other exciting applications involving wafer-scale flexible electronics [41,[73][74][75] as well as highly efficient osmotic energy harvesting cells [24] or recently emerged extension of nanopore sequencing-a nanopore field-effect transistors enabling both ionic and transverse current based biomolecule detection. [15,76,77] We believe that further integration and parallelization of nanopore based membrane devices will lead to high-throughput usage [78][79][80][81] and in turn will encourage new, emerging, commercial applications of this technology.…”
Section: Resultsmentioning
confidence: 99%
“…The design of nanopores in the membranes allows the detection of single molecules. Nanopores have been fabricated into several 2D material based membranes employing different techniques like electron or ions beams, [33][34][35] electroporation, 36 chemical etching, and even the defects created by transferring 2D material sheets synthetized by chemical vapor deposition are used as nanopores for molecules transport. 37,38 The selectivity of the membrane towards the transportation of specific molecules is dependent on the size and distribution of the pores, the surface charge of the membrane and the membrane thickness.…”
Section: Dna Sequencingmentioning
confidence: 99%